A survey of Australian public attitudes towards funding of high cost cancer medicines. Issue 3 (March 2021) - Ghinea, Narcyz; Critchley, Christine; Morrell, Bronwen; Kerridge, Ian; Campbell, Terry; Day, Richard; Gazarian, Madlen; Isaacs, David; Liauw, Winston; Olver, Ian; Pace, Jessica; Pearson, Sallie; et al.
Highlights: New cancer medicines are amongst the most expensive medicines available. Challenging decisions need to be made about access to these medicines. 1039 Australians were surveyed to understand attitudes towards funding these medicines. Australians strongly support government funding of high cost cancer medicines. However, finding the right balance between equity and access remains a challenge. Abstract: Background: In the past decade many novel, and in some cases transformative, cancer medicines have entered the market. Their prices and the amount spent on them by governments have increased rapidly, bringing to the forefront trade-offs that must be made. In this paper we explore the Australian public's attitude towards the funding of high cost cancer medicines (HCCM) to inform reimbursement and health technology assessment (HTA) policy. Methods: A survey consisting of 49 questions about the funding of HCCMs was developed by the investigators. Recruitment was conducted via Qualtrics. 1039 Australian adults completed the survey. Results: The Australian public overwhelmingly supports funding of HCCMs (95.5 %) to enhance equity of access (97.8 %), and to respond to patients' needs (98 %). When respondents were challenged to balance equity versus access in different contexts inconsistencies emerged. Different demographic factors were important in predicting support for various strategies. Conclusion: Our results suggest that the Australian public strongly supports government funding of HCCMs and values both equity and access. Equally, however, the public is uncertain about how equity and access are to be balanced and achieved, and such ambivalence needs to be both further explored and accommodated in policy processes. Our results may be used by policymakers in Australia, and countries with similar systems and values, to further develop policies and processes for funding HCCMs.